Quill mites (Acariformes: Syringophilidae) associated with birds of Mexico - Skoracki, Maciej (Zootaxa, 2017)
The fauna of quill mites of the family Syringophilidae (Acariformes: Cheyletoidea) parasitizing birds in Mexico is surveyed. Three new species of the genus Syringophiloidus Kethley are described: S. amazilia sp. nov. from Amazilia candida (Bonaer & Mulsant) (Apodiformes: Trochilidae), S. cincli sp. nov. from Cinclus mexicanus Swainson (Passeriformes: Cinclidae), and S. sporophila sp. nov. from Sporophila torqueola (Bonaparte) (Passeriformes: Thraupidae). Additionally, six quill mite species are found for the first time in Mexico and several new host associations are recorded. The syringophilid fauna presently recorded in Mexico is summarized.